Strategic prospective: beyond of the strategic plan - Chung Pinzás, Alfonso (2009)
This article focuses its study in diverse analyze techniques of the long term scenarios, all of this answering to the next question how to link the formulation of the strategic plans of one organization to a long term desired future?; for this it analyze and compare three principal tools like the Forecasting, Foresight and the Strategic Prospective, proposing the Strategic Ladder Diagram like the link of the strategic plans and the future scenario.